KPSS v bor'ba za osuščestvlenie programmy stroitel'stva kommunizma. [Pri učast. K.I. Ichsanova, M.A. Zagajnova, V.A. Kovalenko i dr. Pod red. V.L. Ignat'eva] ("Mysl'", 1968)
AON pri CK KPSS. Kafedra istorii KPSS.